Exporting Costs and Multi-Product Shipments - David Gomtsyan; Alexander Tarasov (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In this paper, employing transaction level data for Russian imports, we explore the role of multi-product shipments in explaining shipping patterns across countries. First, we document that firms from more developed countries include on average more different products into a single shipment. We then show that such multi-product shipments can potentially explain why more developed countries tend to have a higher number of shipments per period with a lower average quantity and value. The mechanism considered in the paper is based on that multiproduct shipments allow splitting fixed costs per shipment across many products and, therefore, reducing total shipment costs. As a result, more developed countries tend to have lower fixed costs per shipment. Finally, we construct a simple partial equilibrium model that enables us to quantify the role of multi-product shipments in determining shipping costs.
Keywords: F10; 330; asymmetric trade costs; fixed costs per shipment; advanced countries